Hours of employment of women and young persons employed in factories. Report of a working party of the National Joint Advisory Council on part VI of the Factories Act 1961 and associated legislation. [Forew. by B. Castle] (Her Majesty's Stationery Office, 1969)
Department of Employment and Productivity.